(3ebGdI aj Gdfhe hGdjbXIs - (3LGdjfhSs ((3Nda Hf CHj GdQHjY Hf jMji GdCfOdSi s)
(3ChdgG (B:s
(3bGd LGdjfhS Ef GdCSHGH GdJi jchf efgG gi QWhHI GdOeGZ hcKQI EJSGY eTGYHI s
(3BNQgG (B:s
(3hjchf GdWHjYI CjVkG JUdM GdCYVGA hjHbi YfgGGdHbGjG GdQOjI hjgVe HGbi hbJ gVegG ddeCcd ai MGd Gdfhf Je cJGH LGdjfhS s
(3Vef eLehY , JQJjHgG (B: (3GdebGdI GdNGeSIs
(3YhQV HGdCUd Gdefbhd efg aUM HMSH GdWGbIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs